A temporary Christmas arrangement - Rimmer, Christine (Rimmer, Christine Bravos of Valentine Bay, 2020)
Neither Harper Bravo nor Lincoln Stryker are planning to stay in Valentine Bay. She<U+2019>s got big-city career plans, and he<U+2019>s trying to figure out how to balance work and caring for his orphaned niece and nephew. But when Lincoln moves in next door and needs a hand, a cash-strapped Harper can<U+2019>t help but step in. They make a deal: just during the holiday season, she<U+2019>ll nanny the kids while he works, and then they<U+2019>ll each leave town. But when they can<U+2019>t deny the spark between them, will love be enough to have them both changing their plans?